Development of Woolly Hair and Hairlessness in a CRISPR−Engineered Mutant Mouse Model with KRT71 Mutations - Tao Zhang; Hongwu Yao; Hejun Wang; Tingting Sui (Cells, 2023)
Hypotrichosis simplex (HS) and woolly hair (WH) are rare and monogenic disorders of hair loss. HS, characterized by a diffuse loss of hair, usually begins in early childhood and progresses into adulthood. WH displays strong coiled hair involving a localized area of the scalp or covering the entire side. Mutations in the keratin K71(KRT71) gene have been reported to underlie HS and WH. Here, we report the generation of a mouse model of HS and WH by the co−injection of Cas9 mRNA and sgRNA, targeting exon6 into mouse zygotes. The Krt71−knockout (KO) mice displayed the typical phenotypes, including Krt71 protein expression deletion and curly hair in their full body. Moreover, we found that mice in 3–5 weeks showed a new phenomenon of the complete shedding of hair, which was similar to nude mice. However, we discovered that the mice exhibited no immune deficiency, which was a typical feature of nude mice. To our knowledge, this novel mouse model generated by the CRISPR/Cas9 system mimicked woolly hair and could be valuable for hair disorder studies.